Baby engagement within the traditional ulama of the Madurese ethnicity: a Maṣlaḥa analysis - Ali Imron; Ilyya Muhsin; Mustla Sofyan Tasfiq; Razizi Tarmuji (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2024)
This study delves into the practise of infant betrothals within the traditional Madurese ulama’s lineage, designed to preserve the clerical lineage. However, practical application reveals discrepancies where not all betrothals align with the initially arranged intentions. Instances of mismatches arise due to potential rejection by the children involved. This phenomenon is analysed through the lens of maṣlaḥah-mafsadah. This analysis unveils a nuanced perspective on the Madurese ulama’s tradition of infant betrothal, highlighting its significance beyond local custom to encompass its associated benefits and risks. Employing qualitative methods, this research draws upon in-depth interviews using purposive sampling techniques with Madurese community leaders well-versed in the region’s marital customs. This study finds underscore that infant engagement practises, within Islamic law, do not contravene sharia provisions. The infant betrothal tradition, conducted by the Madurese ethnic ulama’s lineage, aims to fortify kinship bonds among ulama families and identify optimal partners for children, considering familial background and religious erudition. Nevertheless, the study emphasises the imperative to prioritise the interests and preferences of the child throughout the engagement and marriage process.